Parental Involvement and Academic Performance of High School Students with Solo Parents in a Catholic School - Valencia, Emelito L.; Roberto, Johnny T. (Philippine Social Science Journal, 2020)
Parental involvement is the foundation of a child’s education that has been recognized to positively impact students’ academic outcomes. However, a lack of parents’ support and involvement in the children’s education persists in a catholic school in the Philippines. It leads to issues concerning its role in children’s academic performance with single parents. Thus, this study describes the extent of involvement of solo parents based on Epstein’s framework covering parenting, communicating, volunteering, learning at home, decision-making, and collaborating in relation to their demographics. It also describes the level of academic performance of high school students with solo parents in a catholic school during the School Year 2019 – 2020 as a whole and according to the academic level. It also explores the differences in the extent of involvement and level of the students’ academic performance and the relationship between these two variables.